PROGRAM PEMBIASAAN KARAKTER SISWA MELALUI PENDAMPINGAN SEKOLAH PEDALAMAN DI KALIMANTAN TENGAH - Asriana Kibtiyah; Ikhsan Gunadi (LPPM UNIVERSITAS HASYIM ASY'ARI TEBUIRENG JOMBANG, 2020)
Abstract: Schools as the leading education operators have a heavy responsibility as with schoolsin the interior of Central Kalimantan province. Through social responsibility programs, miningcompanies located in rural villages carry out school assistance programs. By involving expertsand practitioners in the world of education, the character habituation mentoring program iscarried out in a measured and planned manner. This study is to describe the original conditions ofthe schools in the interior. This research is qualitative in nature and has a journalistic descriptivecase study background which is expected to reveal the problems of rural schools. In this study, aprocess of testing the ability of teachers and students was also carried out, observing teachercompetence in teaching, and so on. Research data were obtained in addition to field observationsas well as interviews with teachers, students and parents as well as community leaders includingofficials in government and companies. The results showed that the teacher's ability to teach andliterate was relatively low. The findings of this study are regarding the existence of schoolprincipals who do not function in managing schools so that most rural schools run without a cleardirection and purpose. Another finding regarding the culture of local people who do not have theawareness of realizing child-friendly education and educating children to become quality humanbeings is also not an easy thingKeywords: Character Habituation, Outback SchoolAbstrak: Sekolah sebagai operator pendidikan terdepan memiliki tanggung jawab yang tidakringan sebagaimana dengan sekolah-sekolah yang ada di pedalaman provinsi Kalimantan Tengah.Melalui program tanggung jawab sosial, perusahaan tambang yang berada di desa pedalamanmelakukan program pendampingan sekolah. Dengan melibatkan para pakar dan praktisi duniapendidikan, program pendampingan pembiasaan karakter dijalankan secara terukur dan terencana.Penelitian ini untuk mendeskripsikan kondisi asli sekolah-sekolah di pedalaman. Penelitian inibersifat kualitatif dan berlatarbelakang studi kasus deskriptif jurnalistik yang diharapkan dapatmengungkapkan permasalahan sekolah pedalaman. Dalam penelitian ini juga dilakukan prosespengujian atas kemampuan guru maupun siswa, mengobservasi kompetensi guru dalam mengajar,dan sebagainya. Data penelitian diperoleh selain melalui pengamatan lapangan juga wawancarakepada guru, siswa dan orangtua serta para tokoh masyarakat termasuk pejabat di Pemerintahanmaupun perusahaan. Hasil penelitian menunjukkan bahwa kemampuan guru masih terbilangrendah dalam mengajar dan berliterasi. Temuan penelitian ini terhadap keberadaan kepala sekolahyang tidak berfungsi mengelola sekolah sehingga sebagian besar sekolah pedalaman berjalan tanpaarah dan tujuan yang jelas. Temuan lain berkenaan budaya masyarakat setempat yang belummemiliki kesadaran mewujudkan pendidikan yang ramah anak, dan mendidik anak menjadimanusia berkualitas juga bukan hal yang mudah.Kata Kunci: Pembiasaan Karakter, Sekolah Pedalaman